Initial outcomes of local anaesthetic freehand transperineal prostate biopsies in the outpatient setting. (3rd December 2019) - Kum, Francesca; Elhage, Oussama; Maliyil, Jed; Wong, Kathie; Faure Walker, Nicholas; Kulkarni, Meghana; Namdarian, Benjamin; Challacombe, Benjamin; Cathcart, Paul; Popert, Rick
Abstract : Objectives: To evaluate the histopathological outcomes, morbidity and tolerability of freehand transperineal (TP) prostate biopsies using the PrecisionPoint™ access system (Perineologic, Cumberland, MD, USA) under local anaesthetic (LA) in the day surgery and outpatient environments, as systematic and targeted biopsies can be taken with the potential for reduced morbidity, particularly sepsis. Patients and Methods: In all, 176 patients underwent freehand TP prostate biopsies from May 2016 to November 2017. The procedure was carried out either under LA alone or with the addition of sedation. Magnetic resonance imaging (MRI) scans were reported using the Prostate Imaging‐Reporting and Data System (PI‐RADS), version 2. Tolerability was assessed using a visual analogue scale pain score for each procedural stage. Histopathological outcomes and complications were recorded. Results: The mean (range) age was 65 (36–83) years, median (range) prostate‐specific antigen level was 7.9 (0.7–1374) ng/mL, and the mean (range) prostate volume 45 (15–157) mL. Biopsies were taken under LA alone (160 patients, 90%) or under LA with sedation (16, 9%). The main indication for biopsy was primary diagnosis (88.6%). In all, 91 (52%) patients underwent systematic TP biopsies (mean 24.2 cores). Cognitive MRI‐targeted biopsies alone were performed in 45 patients (26%; mean 6.8 cores), and 40 (23%) had both systematic and target biopsies (mean 27.9 cores). Of the 75 patients who had primary systematic biopsies alone, 46 (61%) were positive, and 28/46 (60.9%) were diagnosed with clinically significant disease (Gleason ≥3+4). VAS pain scores were greatest during LA administration. There were five complications (2.8%,  Clavien–Dindo Grade I/II). No patients developed urosepsis. Conclusions: Freehand TP biopsies using the PrecisionPoint access system is a safe, tolerable and effective method for systematic and targeted biopsies under LA in the outpatient setting. It has replaced transrectal biopsies in our centre and has potential to transform practice.